Effects of titanium dioxide quantum dots on the color deviation and luminous flux of white light-emitting diodes - Thanh Binh Ly; Phung Ton That; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
The application of quantum dots has been considered as a promising approach to the advancement of phosphor-converted light-emitting diodes (pc-LEDs) since they perform an excellent extinction coefficient. Yet, it is challenging to manage their influences on the optical properties of LEDs due to their different nanometers in size. Hence, the object of this research is to analyze the influences of quantum dot (QDs) to figure out the solution to control the enhancement of LED lighting performances. Particularly, the study worked on investigating the scattering and absorption features of titanium dioxide (TiO2) QDs. It demonstrated that the radiant efficiency and luminous stability of the TiO2 QDs-converted LEDs (QC-LEDs) was inferior due to the strong light absorption and reabsorption occurring inside the LED packages. Additionally, it also presented low uniformity of color distribution because the scattering ability of QDs is weak. Therefore, reducing the concentration of QDs when adding to the LED structure seems to be possible to enhance the luminous output of QC-LEDs. We propose 0.05% wt. TiO2 for white LED to reduce the illumination losing caused by re-absorbent and total internal backscattering, resulting in approximate 31% lumen improvement and high color rendering index (CRI) measured at about 85, at a high color temperature of 7500 K.